The role of texture on superelasticity and elastocaloric effect in severely rolled Ti-44Ni-5Cu-1Al (at%) shape memory alloy. (1st March 2022) - Hou, Ruihang; Xiao, Fei; Li, Zhu; Jin, Xuejun
Abstract: The effects of crystallographic texture on the superelasticity and elastocaloric effect of nanograin Ti-44Ni-5Cu-1Al rolled sheet are investigated. Stress-strain curves with different orientation angles between tensile direction and rolling direction show that the tensile strain of the sheet is largest in rolling direction (RD) along <110> and smallest in transverse direction (TD) parallel to <100>. This texture dependence is further studied by analyzing the evolution of each strain component. With the increase of the orientation angle, intergranular constraint effect reaches the maximum in TD. As a result, transformation strain and adiabatic temperature change have a similar monotonic decreasing trend. The material coefficient of performance of the sheet reaches 11.2 in RD. This value makes it possible for severely rolled Ti-44Ni-5Cu-1Al sheet to be a potential candidate for solid-state refrigeration application at room temperature. Abstract : Image, graphical abstract